A Protocol for the Computational Design of High Affi nity Molecularly Imprinted Polymer Synthetic Receptors - Kal Karim; Todd Cowen; Antonio Guerreiro; Elena Piletska; Michael J Whitcombe; Sergey A Piletsky (Global Journal of Biotechnology and Biomaterial Science - Peertechz Publications, 2017)
Molecularly imprinted polymer (MIP) nanoparticles, commonly referred to as 'plastic antibodies' or synthetic receptors, are polymeric materials with strong affinity and selectivity for a particular chemical target.MIPs are regularly produced for use in sensors for monitoring food quality and environmental  pollutants,  and  in  the  design  of  robust  and  affordable  replacements  for  biological  receptors,  enzymes and  antibodies  in  drug  testing  and  assays.  More  recently  the  easy  production  of  MIP  nanoparticles has also permitted research relating to possible in vivo applications, primarily in drug delivery systems, toxin sequestration and pathogen inhibition. The strength of the interaction between the target and the polymer binding site is dependent on the particular monomers selected in synthesis of the MIP, and the relative  concentrations  of  these in the pre-polymerization  mixture.  While  computational  approaches have been used to aid in MIP design previously, the methods adopted are often slow and  simplistic,centring on observations of the template structure with a couple of functional monomers presumed to be appropriate. We present here an automated method of rapidly screening numerous functional monomers and  effectively  determining  appropriate  monomer  ratios,  while  accounting  for  spatial  discrimination in  selection  and  dynamic  parameters  in  optimization.  Example  are  then  given  of  effect  MIP  synthesis resulting from the protocol, and the benefits of this approach over competing methods are discussed.